Suppression of P53 Pathway is an Important Factor Inducing Acute Graft-versus-Host Disease Through T Cell Activation Based on Bioinformatics Analysis - Wang S; Qin W; Cheng T; Zeng C; Chen X; Xu Y (Dove Medical Press, 2024)
Shiyu Wang,1- 4 Wei Qin,1- 4 Tingting Cheng,1- 4 Cong Zeng,1- 4 Xu Chen,1- 4 Yajing Xu1- 4 1Department of Hematology, Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 2National Clinical Research Center for Geriatric Diseases (Xiangya Hospital), Changsha, Hunan, People's Republic of China; 3Hunan Hematologic Neoplasms Clinical Medical Research Center, Changsha, Hunan, People's Republic of China; 4National Clinical Research Center for Hematologic Diseases, the First Affiliated Hospital of Soochow University, Soochow, Jiangsu, People's Republic of ChinaCorrespondence: Yajing Xu, Department of Hematology, Xiangya Hospital, Central South University, #87 Xiangya Road, Changsha, Hunan, People's Republic of China, Email xyyajingxu@csu.edu.cnPurpose: Acute graft-versus-host disease (aGVHD) poses a significant impediment to achieving a more favourable therapeutic outcome in allogeneic hematopoietic stem cell transplantation (allo-HSCT). The tumour suppressor p53 plays a pivotal role in preventing aGVHD development. However, whether P53 pathway which contains p53 family members and other related genes participates in aGVHD development remains an unsolved question.Patients and Methods: Transcriptomic data was obtained from Gene Expression Omnibus (GEO) database. Gene set enrichment analysis was applied to determine the enrichment degree of signaling pathways. CIBERSORT and ssGSVA were used to evaluate immune cell compositions. Univariate and multivariate logistic regression analysis were performed to examine the independent diagnostic variables. qRT-PCR was utilized to validate the genes expression levels in our cohort.Results: A total number of 102 patients (42 aGVHD patients vs 60 non-aGVHD patients) were obtained after integrating two datasets in GEO database (GSE73809 and GSE4624). P53 pathway was remarkably suppressed in T cells from aGVHD patients and negatively associated with activated T cells as well as T cells activation related signaling pathways, including T-cell receptor (TCR), mTORC1, MYC and E2F target pathways. A risk model for aGVHD built by four genes (DDIT3, FBXW7, TPRKB and TOB1) in P53 pathway, exhibiting high differentiate and predictive value. DDIT3 and FBXW7 mRNA expression levels significantly decreased in peripheral blood mononuclear cells (PBMCs) from aGVHD patients compared with non-aGVHD group in our patient cohort, consisting with bioinformatics analysis.Conclusion: P53 pathway plays a potential role in impeding T cell activation through suppressing its related signaling pathways, thereby preventing aGVHD development. P53 pathway may emerge as a promising therapeutic target in aGVHD treatment.Keywords: allogeneic hematopoietic stem cell transplantation, aGVHD, P53 pathway, T cells, activation